Life-threatening Double-J stent migration with helicoidal appearance: Length matters. Issue 2 (May 2020) - Lorusso, Vito; Palmisano, Franco; Morelli, Michele; Spinelli, Matteo Giulio; Dell'Orto, Paolo Guido; Montanari, Emanuele
Background: The Double-J stent is one of the most commonly used devices in urologic practice. Due to its widespread use, numerous common complications have been reported, such as irritative symptoms, infection, and encrustation. More rare complications have also been described, such as up or downward migration and displacement outside the urinary tract. We present a rare case of downward migration of a Double-J stent in a 21-year-old Caucasian female. Case Presentation: A 21-year-old female with a solitary kidney presented to the emergency department with acute renal failure, left flank pain, and fever. She had undergone left Double-J stenting 1 week earlier in her homeland for left renal colic and anuria. A kidney–ureter–bladder X-ray revealed a 10-mm lumbar ureteral stone and the proximal coil of the Double-J stent making multiple loops along the ureter, resulting in a helical appearance. She underwent surgery to remove the previous stent and to place a new one. She was discharged 2 days later and her renal function had returned to normal values at her 1-week follow-up. Conclusions: Double-J Stent placement is a common procedure in the management of urinary tract diseases but is not devoid of life-threatening complications. Regular follow-up of stents and on-time evaluation of clinical complaints are mandatory for an aggressive treatment of complications.